2021
DOI: 10.1109/tbme.2020.3020358
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Estimation of Acute Changes in Preload Using Epicardially Attached Accelerometers

Abstract: Objective: A miniaturized accelerometer can be incorporated in temporary pacemaker leads which are routinely attached to the epicardium during cardiac surgery and provide continuous monitoring of cardiac motion during and following surgery. We tested if such a sensor could be used to assess volume status, which is essential in hemodynamically unstable patients. Methods: An accelerometer was attached to the epicardium of 9 pigs and recordings performed during baseline, fluid loading, and phlebotomy in a closed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…These results significantly extend the application of mechano-sensors in estimating cardiac function, which is so far largely limited to optimization of pacemaker settings by the SonR system ( 15 , 23 ), without the knowledge of absolute values of pressures. Another study on pigs showed that an epicardially placed accelerometer can be used to assess changes in preload, and so filling status, using the frequency of myocardial acceleration ( 24 ). In preclinical studies, Thakur et al showed that analysis of S1 and S3 amplitude signals from accelerometers integrated into an implanted pacemaker device was able to monitor the change of absolute left atrial pressure over time ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results significantly extend the application of mechano-sensors in estimating cardiac function, which is so far largely limited to optimization of pacemaker settings by the SonR system ( 15 , 23 ), without the knowledge of absolute values of pressures. Another study on pigs showed that an epicardially placed accelerometer can be used to assess changes in preload, and so filling status, using the frequency of myocardial acceleration ( 24 ). In preclinical studies, Thakur et al showed that analysis of S1 and S3 amplitude signals from accelerometers integrated into an implanted pacemaker device was able to monitor the change of absolute left atrial pressure over time ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional data from previous studies in 24 porcines (44 ± 4 kg SD) were used for validation of the accuracy of the accelerometer-based method for estimations of the LV pressure trace and pressure-displacement loop. These studies included measurements from 15 open chest 9,17 and 9 closed chest porcines 18 , the latter included to test the method also under closed chest conditions. The animals were anesthetized and surgically prepared as previously described 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Data comprised recordings from 19 ID: 8628 and 9303]. They were acute experiments where the animals were ventilated and surgically prepared as previously described [3], [27], [28]. The experiments followed different instrumentation protocols, but all of them had left ventricular pressure (LVP) and acceleration signals recorded simultaneously during different interventions.…”
Section: A Data Acquisitionmentioning
confidence: 99%